INFORMATION CULTURE OF EDUCATION MANAGER: LEVEL AND FACTOR ANALYSIS - Koshevenko, Svetlana; Silchenkova, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article presents the results of a monographic research of information culture of  educational manager. The article includes the author's definition of the concept of "information culture  of education manager", the functional model of information culture of educational manager consisting of following components: motivational, normative-valuable, cognitive-operational, communicative, informational, critical, educational and creative. The article includes information about level and factor analysis of information culture of educational manager, detection of the main components affecting the information culture of educational manager and their dependence.